IMPLEMENTASI REPLACEMENT STRATEGY STEADY STATE DAN GENERATIONAL DALAM ALGORITMA BEREVOLUSI UNTUK PENYELESAIAN TSP - Munawir Munawir; Taufiq A. Gani; Yuwaldi Away (Universitas Syiah Kuala, 2016)
Travelling salesman problem is the traveling salesman optimization problems in visiting the city and every town just skipped right one. TSP problem can be applied to various cases that are to optimize, in the completion of TSP there are several methods that can be used, including the algorithms evolve. To improve the quality of the solution, the method used is the strategy of steady state and generational turnover. This research analyzes the methods of steady state strategy and generational turnover for the completion of TSP. Test data used is the data tsplib as much as 10 datasets with the number of cities between 51 to 100 cities, resulting from this testing is the average distance from each dataset. Keywords – Algorithm Evolved, TSP, Replacement Strategy, Steady State, generational